2018
DOI: 10.1111/cbdd.13352
|View full text |Cite
|
Sign up to set email alerts
|

Novel 1,3‐oxazine‐tetrazole hybrids as mushroom tyrosinase inhibitors and free radical scavengers: Synthesis, kinetic mechanism, and molecular docking studies

Abstract: A variety of 5-(2H-tetrazol-5-yl)-4-thioxo-2-(substituted phenyl)-4,5-dihydro-1,3-oxazin-6-ones (3a-k) have been synthesized from 1,3-oxazine-5-carbonitriles (2a-k). The protocol represents an efficient, facile, and novel route from easily available precursors to unprecedented structures that share 1,3-oxazine and tetrazole motifs of utmost value. All the synthesized compounds (3a-k) were evaluated for their inhibitory potential against mushroom tyrosinase. Results revealed that all examined 1,3-oxazine-tetraz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 45 publications
1
7
0
Order By: Relevance
“…The predicted chemo-informatic properties such as molecular weight (g/mol) HBD, HBA, LogP, polar surface area (PSA), molar volume and a drug-likeness score of ligand molecules were obtained. It has been confirmed from previous research data that the standard value for molecular weight is (≤500 g/mol) [ 19 ]. The computational results showed that our compounds possessed good molecular weight compared to the standard value (500 g/mol).…”
Section: Resultssupporting
confidence: 65%
“…The predicted chemo-informatic properties such as molecular weight (g/mol) HBD, HBA, LogP, polar surface area (PSA), molar volume and a drug-likeness score of ligand molecules were obtained. It has been confirmed from previous research data that the standard value for molecular weight is (≤500 g/mol) [ 19 ]. The computational results showed that our compounds possessed good molecular weight compared to the standard value (500 g/mol).…”
Section: Resultssupporting
confidence: 65%
“…So far, several azole derivatives (Figure 13) have been studied for their tyrosinase inhibitory activity 388 . The discovered new types of inhibitors included DL-3(5-benzazolyl) alanines and alpha-methyldopa analogs 389 , aryl pyrazoles 390 , heterocyclic hybrids based on pyrazole and thiazolidinone scaffolds 391 , 3,5-diaryl-4,5-dihydro-1H 392 and 3,5-diaryl pyrazole derivatives 393 , pyrazolo[4,3-e][1,2,4]triazine sulfonamides and sildenafil 394–396 , 1,3-oxazine-tetrazole 397 , indole-spliced thiadiazole 398 , benzimidazole-1,2,3-triazole hybrids 399 , 1,2,3-triazole-linked coumarinopyrazole conjugates 400 , isoxazolone derivatives 401 5(4H)-oxazolone derivative 402 , imidazolium ionic liquids 403 , thiazolyl resorcinols 404 have demonstrated the inhibitory effect on tyrosinase. Furthermore, some thiazolidine derivatives have been evaluated for their tyrosinase inhibitory activity including azo-hydrazone tautomeric dyes substituted by thiazolidinone moiety 405 , (Z)-5-(2,4-dihydroxybenzylidene) thiazolidine-2,4-dione 406 , 5-(substituted benzylidene) thiazolidine-2,4-dione derivatives 407 , (2RS,4R)-2-(2,4-dihydroxyphenyl)thiazolidine-4-carboxylic acid 408 , 2-(substituted phenyl) thiazolidine-4-carboxylic acid derivatives 409 and (Z)-5-(3-hydroxy-4-methoxybenzylidene)-2-iminothiazolidin-4-one 410 .…”
Section: Inhibitors From Natural Semisynthetic and Synthetic Sourcesmentioning
confidence: 99%
“…Over the past several years, our laboratory has reported various phenolic derivatives including tyramine, thymol, vanillin, carvacrol, and coumarin analogues which structurally mimic the natural substrates of the enzyme tyrosinase stronger than the L-tyrosine and L-DOPA [26][27][28][29][30]. We concluded from these investigations that substitution pattern of phenolic hydroxyls is directly related to degree of tyrosinase inhibition.…”
Section: Introductionmentioning
confidence: 99%